Vocational education and training in Europe : Germany - Hippach-Schneider, Ute [Verfasser]; Huismann, Adrienne [Verfasser] (Cedefop ReferNet Germany, 2019)
"This country report is part of a series of reports on vocational education and training produced for each EU Member State plus Norway and Iceland by members of ReferNet, Cedefop's European network of expertise in vocational education and training. This VET in Europe report provides readers with a concise, basic insight into the state of the vocational education and training system of Germany. It situates the German education and training system within a broad political, social, economic, and labour market framework." (Editor, BIBB-Doku)
Keywords: S System beruflicher Bildung; S 1.3 Berufliche Erstausbildung; S 2.3 Berufsbildungspolitik; S 1.5.2 Berufliche Weiterbildung; S 4.1 Finanzierungsquellen; Berufsbildungssystem; Berufsbildungspolitik; Berufsausbildung; Berufliche Weiterbildung; Bildungsfinanzierung; Bundesrepublik Deutschland